Recent advances in the synthesis and characterisation of methylated chitosan derivatives - Boymirzaev, Azamat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The synthesis, characterization, and physicochemical characteristics of water-soluble methylated chitosan derivatives are the main topics of this research. There are several uses for trimethylchitosan and N-[(2-hydroxyl-3-trimethyl ammonium) ргоруl] chitosan (HTCC) in biomedicine, and the degree of quaternization has a significant impact on the physicochemical characteristics of HTCC. N,O-substituted quaternized chitosan is frequently obtained by directly replacing the hydrogen atoms from the associated amino and hydroxyl functional groups from chitosan at the C6 position with glycidyl trimethylammonium chloride (GTMAC).